Melampaui Pembelajaran Formal di Kelas: Model Imersi Total untuk Mempercepat Akuisisi Bahasa Arab pada Penutur Non-Arab - Kudus, Ruhul; Salim Al Busaidi (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2026)
Academic documentation on the effectiveness of intensive language institute models in the Middle East for accelerating second language acquisition remains limited, as previous literature has predominantly focused on independent digital strategies or traditional formal classrooms. This qualitative single-case study aims to comprehensively analyze the Arabic teaching system for non-native speakers at the Sultan Qaboos Institute, Oman. Data were gathered through semi-structured interviews with teachers, students, and curriculum administrators, supported by classroom observations and curriculum document analysis. The findings reveal six integrated strategic pillars: CEFR-based placement standardization, pedagogical personalization through differentiated and competency-based learning, total immersion methods, interactive assimilation with native speakers (language partners), contextual environmental-based external laboratories within real sociocultural settings, and the holistic construction of a macro-language ecosystem. These findings conceptually demonstrate that accelerative functional Arabic acquisition is not achieved through isolative grammar instruction, but rather through the creation of an interlanguage continuum that converges Second Language Acquisition (SLA) theory with culture-rooted experiential learning. This study offers a replicable sociocultural pedagogical blueprint for global language institutions..